The MassGeneral Hospital for Children Adolescent Medicine Handbook - Goldstein, Mark A.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
The MassGeneral Hospital for Children Adolescent Medicine Handbook, is a definitive, practical guide for the optimal clinical care of adolescents. This unique and invaluable resource is not only replete with user-friendly diagrams, tables, charts and pathways; it most importantly covers in detail the best practices in adolescent medicine where practice not only means the most appropriate approaches, diagnostic evaluation and best treatments, but also the best ways to connect, communicate and continue care with teenagers. Divided into three sections, the handbook covers general adolescent medicine, sexuality, and mental health. Chapters are written by outstanding physician authors who represent expertise in pediatric or adult specialties and have taught or trained at Massachusetts General Hospital. The MassGeneral Hospital for Children Adolescent Medicine Handbook joins together the collective knowledge and wisdom of its esteemed contributors to provide a multi-specialty approach to adolescent healthcare that balances the science and the art of adolescent medicine.
Adolescent Preventive Services -- The Adolescent Patient Interview -- Tanner Staging -- NormalAdolescent Development -- Male Genitourinary Exam -- Adolescent Dermatology -- Obesity -- Adolescent Nutrition, IBD, IBS -- Sports Injuries in the Adolescent -- Cardiac Issues in Adolescence -- Menstrual Irregularities -- Basics of Hormonal Contraception -- Adolescent Pregnancy -- Polcystic Ovary Syndrome -- Sexually Transmitted Infections in Adolescents -- Delayed Puberty, Short Stature and Tall Stature -- Adolescent Substance Abuse -- Adolescent Mental Health Disorders -- Eating Disorders -- Adolescent Relationship Violence in Clinical Settings -- Bullying -- Transition of Care -- Appendix.
Keywords: Medicine; Family medicine; Public health; Internal medicine; Pediatrics; Emergency medicine; Philosophy (General).; Medicine & Public Health; Pediatrics; Internal Medicine; General Practice / Family Medicine; Primary Care Medicine; Psychology, general; Public Health